The GUL-1 Protein Binds Multiple RNAs Involved in Cell Wall Remodeling and Affects the MAK-1 Pathway in Neurospora crassa - Herold, Inbal; Zolti, Avihai; Garduño-Rosales, Marisela; Wang, Zheng; López-Giráldez, Francesc; Mouriño-Pérez, Rosa R.; Townsend, Jeffrey P.; Ulitsky, Igor; Yarden, Oded (Frontiers in Fungal Biology, 2021)
The Neurospora crassa GUL-1 is part of the COT-1 pathway, which plays key roles in regulating polar hyphal growth and cell wall remodeling. We show that GUL-1 is a bona fide RNA-binding protein (RBP) that can associate with 828 “core” mRNA species. When cell wall integrity (CWI) is challenged expression of over 25% of genomic RNA species are modulated (2628 mRNAs, including the GUL-1 mRNA). GUL-1 binds mRNAs of genes related to translation, cell wall remodeling, circadian clock, endoplasmic reticulum (ER), as well as CWI and MAPK pathway components. GUL-1 interacts with over 100 different proteins, including stress-granule and P-body proteins, ER components and components of the MAPK, COT-1, and STRIPAK complexes. Several additional RBPs were also shown to physically interact with GUL-1. Under stress conditions, GUL-1 can localize to the ER and affect the CWI pathway—evident via altered phosphorylation levels of MAK-1, interaction with mak-1 transcript, and involvement in the expression level of the transcription factor adv-1. Therefore, GUL-1 functions in multiple cellular processes, including the regulation of cell wall remodeling, via a mechanism associated with the MAK-1 pathway and stress-response.